2020
DOI: 10.3390/nu12113377
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Associated to Better Survival in Hospitalized Frail Elderly COVID-19 Patients: The GERIA-COVID Quasi-Experimental Study

Abstract: Background. The objective of this quasi-experimental study was to determine whether bolus vitamin D supplementation taken either regularly over the preceding year or after the diagnosis of COVID-19 was effective in improving survival among hospitalized frail elderly COVID-19 patients. Methods. Seventy-seven patients consecutively hospitalized for COVID-19 in a geriatric unit were included. Intervention groups were participants regularly supplemented with vitamin D over the preceding year (Group 1), and those s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
255
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(296 citation statements)
references
References 29 publications
13
255
2
11
Order By: Relevance
“…This present analysis follows in the footsteps of tentative evidence derived from a recent prospective study [ 30 ] and three clinical trials [ 31 , 32 , 33 ], two of which have shown benefit (one did not observe any effect) in patients hospitalized with COVID-19 following vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This present analysis follows in the footsteps of tentative evidence derived from a recent prospective study [ 30 ] and three clinical trials [ 31 , 32 , 33 ], two of which have shown benefit (one did not observe any effect) in patients hospitalized with COVID-19 following vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In the quasi-experimental prospective study by Annweiler and colleagues, patients hospitalized for proven COVID-19 were stratified into three groups: Group 1, in which vitamin D was regularly supplemented during the 12 months prior to diagnosis; Group 2 in which vitamin D was given soon after hospital admission and Group 3, in which patients were not treated with vitamin D. Those who were supplemented with vitamin D after a diagnosis of COVID-19 did not show any significant benefit compared to untreated controls [ 30 ]. Instead, patients who regularly received bolus vitamin D3 supplementation in the preceding 12 months experienced a significantly lower mortality rate over 14 days (HR: 0.07, p = 0.017) compared to the control group (without vitamin D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the effects of standard care with and without oral calcifediol [25(OH)D; 0.532 mg on day of admission, 0.266 mg on days 3 and 7 then weekly] were compared in 76 people admitted to a Spanish hospital for COVID-19, reduced risk for admission to intensive care was observed for those treated with calcifediol (OR 0.03, 95% CI 0.003–0.25, after adjusting for prevalence of hypertension and type-2 diabetes) ( 264 ). From two “quasi-experimental” French studies, regular supplementation with “bolus” vitamin D [e.g., 80,000 IU vitamin D every 2–3 months ( 265 )] prior to disease onset, reduced the risk of death from COVID-19 in both hospitalized patients [ n = 77: HR 0.07 95% CI 0.01–0.61 ( 266 )], and people living in a nursing home [ n = 66: HR 0.11 95% CI 0.03–0.48 ( 265 )] with models adjusted for age, gender and other factors. A limitation of these studies was that not all SARS-CoV-2 infections were confirmed by PCR.…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…There are studies demonstrating that COVID-19 patients have lower vitamin D levels with average plasma concentrations about half that of controls. Therefore, vitamin D supplementation is recommended to improve immunity against COVID-19 and reduce human deaths [32] , [33] , [34] , [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%